Behavior problems in children of parents with alcohol and substance use disorder - Kantaş Yılmaz, Fatma; Ergelen, Mine; Bilici, Rabia; Akülker, Gizem (Journal of Dependence, 2021)
Objective: This study was conducted to determine behavioral problems of children of parents with alcohol and substance use disorder.Method: The study included 60 male parents (mean age 39±7,5 years) who had been admitted to the substance addiction clinic and who had children 6 to 18 years of age. The parents were administered the Conners Parent Rating Scale, The Turgay DSM-III Based Disruptive Behavior Disorders Child and Adolescent Rating and Screening Scale and Clinical Interview for DSM-III Axis II Disorders (SCID-II).Results: According to the Conners' Parent Rating Scale, behavioral problems of children included attention deficit disorder/hyperactivity (51,7%), learning difficulty (45%), anxiety (41,7%), psychosomatic problems (20%), behavioral problems (15%). Twenty-eight parents (47,5%) had personality disorders, the majority of whom (85,7%) had B type personality disorders. The frequency of attention deficit disorder/hyperactivity (87,5%) was significantly higher among children whose parents had a history of incarceration and the frequencies of learning problem (%69,2) and anxiety problems (%61,9) were significantly higher among children whose parents had a history of substance use.Conclusion: Attention deficit disorder/hyperactivity, learning problem and anxiety problems were the most common behavioral problems of children whose parents had alcohol and substance use.
Keywords: Alcohol use disorder; substance use disorders; behavioral problem